2003
DOI: 10.1121/1.1525288
|View full text |Cite
|
Sign up to set email alerts
|

The synergy between speech production and perception

Abstract: Speech intelligibility is known to be relatively unaffected by certain deformations of the acoustic spectrum. These include translations, stretching or contracting dilations, and shearing of the spectrum (represented along the logarithmic frequency axis). It is argued here that such robustness reflects a synergy between vocal production and auditory perception. Thus, on the one hand, it is shown that these spectral distortions are produced by common and unavoidable variations among different speakers pertainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…However, in these studies, the very base of the cochleas (coding in humans for frequencies above 5 kHz) has never been carefully observed and the results are far from quantitative. Interestingly, the frequency range of MOC inhibition corresponds to the frequency spectrum of human speech (27). One explanation may be that the MOC efferents facilitate speech perception and understanding while inhibiting nonrelevant stimuli such as background noise (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, in these studies, the very base of the cochleas (coding in humans for frequencies above 5 kHz) has never been carefully observed and the results are far from quantitative. Interestingly, the frequency range of MOC inhibition corresponds to the frequency spectrum of human speech (27). One explanation may be that the MOC efferents facilitate speech perception and understanding while inhibiting nonrelevant stimuli such as background noise (28).…”
Section: Discussionmentioning
confidence: 99%
“…the qualities of each of the elements oriented to an effective production/perception transaction (Ru et al 2003, Tatham & Morton 2006. In order to test these hypotheses, we conducted a production experiment in which the data obtained for each of the two focal conditions and for the three languages respectively were analysed acoustically.…”
mentioning
confidence: 99%
“…The implication was this particular representation of articulatory patterns did indeed exploit the acoustic sensitivity of the vocal tract. At nearly the same time, Ru et al (2003) reported a similar sinusoidal model of the area function that was also based on the Harshman et al factors. Whereas the goals of this study were different than Fitch et al, an equivalence between the acoustic characteristics of the vocal tract and the sinusoidal components was noted.…”
Section: Introductionmentioning
confidence: 71%